APLIKASI FORMULASI AZADIRACHTA INDICA DAN HYPERICUM PERFORATUM TERHADAP PROSES PENYEMBUHAN ULKUS DIABETIKUM (Media Dermato Venereologica Indonesiana, 2020)
Azadirachta indica (neem) and Hypericum perforatum formulation have been used for centuries in traditional medicine. Neem oil contains diterpenoid and triterpenoid, while Hypericum perforatum flower oil extract is quite popular as a treatment for excoriations, wounds, and bruises. Both of these plant extracts have bacteriostatic, antifungal, immunomodulatory, and antiinflammatory effects, and also safe to use as an external treatment for wounds. Several studies have shown the benefit of this formulation for diabetic foot ulcer. A 41- year-old woman had a wound on her right leg that had not been healed for the past two months. Dermatological examination showed an ulcer with an irregular border, measuring 7.5x3.4x0.3 on the lateral region of the right foot. The ulcer’s edge was elevated, while the wall was gently sloping. The surrounding skin was unaffected. The base of the ulcer consisted of granulation tissue and was clean, without any pus formation. The ulcer was painless and odorless. Laboratory tests showed hyperglycemia and hypercholesterolemia. Doppler ultrasound examination showed deep vein thrombosis in the right leg.A topical formulation containing Azadirachta indica and Hypericum perforatum was given. After 49 days of therapy, diabetic ulcer wounds had healed completely.